2016
DOI: 10.1016/j.chemosphere.2015.09.098
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate flame retardants and novel brominated flame retardants in home-produced eggs from an e-waste recycling region in China

Abstract: h i g h l i g h t sEH-TBB, BEH-TEBP and PFRs were measured in free-range chicken eggs. Chlorinated PFRs had higher detection frequencies than non-chlorinated PFRs in eggs. TPHP had a higher detection frequency in albumen; BEH-TEBP was higher in yolks. Dust ingestion is a more important pathway than egg intake in human exposure to PFRs. a r t i c l e i n f o b s t r a c tPhosphate flame retardants (PFRs) and novel brominated flame retardants (NBFRs) (2-ethylhexyl-2,3,4,5-tetrabromo-benzoate (EH-TBB) and bis-(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…For volatile or semi-volatile PEFRs (e.g., TCEP, tris(1-chloro-2propyl) phosphate -TCIPP), air and suspended particles inhalation may be a significant intake pathway (Schreder et al, 2016;Xu et al, 2016;He et al, 2018c). Ingestion of contaminated food (e.g., by migration from plastic packaging) may contribute to oral intake of PEFRs, but its contribution appears to vary substantially between compounds, as well as between and within populations (Zhang et al, 2016;Zheng et al, 2016;Xu et al, 2017;Poma et al, 2017Poma et al, , 2018.…”
Section: Environmental Occurrence and Routes Of Exposurementioning
confidence: 99%
“…For volatile or semi-volatile PEFRs (e.g., TCEP, tris(1-chloro-2propyl) phosphate -TCIPP), air and suspended particles inhalation may be a significant intake pathway (Schreder et al, 2016;Xu et al, 2016;He et al, 2018c). Ingestion of contaminated food (e.g., by migration from plastic packaging) may contribute to oral intake of PEFRs, but its contribution appears to vary substantially between compounds, as well as between and within populations (Zhang et al, 2016;Zheng et al, 2016;Xu et al, 2017;Poma et al, 2017Poma et al, , 2018.…”
Section: Environmental Occurrence and Routes Of Exposurementioning
confidence: 99%
“…In a brominated flame retardant production area in China, decabromodiphenyl ether (BDE-209) was detected in air and diet, and in addition, BDE-209 was found to be the dominant compound found to be present as a result of inhalation . In another study in China, egg consumption was suggested to be a pathway for exposure to BDEs (Zheng et al 2015). One or more BDEs have been detected in breast milk (Chao et al 2010;Dimitriadou et al 2016;Kim et al 2012).…”
Section: Sources Of Exposure To Polybrominated Diphenyl Ethers and Gementioning
confidence: 98%
“…The highest PBDE concentrations were detected in fish, processed foods and fish feeds [56]. In home produced eggs from e-waste sites in China, EH-TBB and BEH-TEBP were found in low concentrations in 50% of chicken egg samples, ranged between <dl-1.82 and 1.17-2.6 ng/g for EH-TBB and BEH-TEBP, respectively [57]. bioaccumulative) had detection frequencies higher than 55% in both serum and human milk samples, while detection frequencies for other BFRs were lower than 30%.…”
Section: Levels Of Pbdes and Nbfrs In Biota And Foodmentioning
confidence: 99%